Sure! Let's solve both systems of equations by substitution.
Q1:
Equations:
- \( y = 4x - 9 \)
- \( y = x - 3 \)
Step 1: Set the equations equal to each other.
Since both equations equal \( y \), we can set them equal to each other:
\[ 4x - 9 = x - 3 \]
Step 2: Solve for \( x \).
\[ 4x - x = -3 + 9 \]
\[ 3x = 6 \]
\[ x = 2 \]
Step 3: Substitute \( x \) back into one of the original equations to find \( y \).
Using \( y = x - 3 \):
\[ y = 2 - 3 \]
\[ y = -1 \]
Solution for Q1:
\( (x, y) = (2, -1) \)
Q2:
Equations:
- \( 4x - y = 20 \)
- \( y = -x + 5 \)
Step 1: Substitute the expression for \( y \) from the second equation into the first equation.
\[ 4x - (-x + 5) = 20 \]
\[ 4x + x - 5 = 20 \]
\[ 5x - 5 = 20 \]
Step 2: Solve for \( x \).
\[ 5x = 20 + 5 \]
\[ 5x = 25 \]
\[ x = 5 \]
Step 3: Substitute \( x \) back into the second equation to find \( y \).
Using \( y = -x + 5 \):
\[ y = -5 + 5 \]
\[ y = 0 \]
Solution for Q2:
\( (x, y) = (5, 0) \)
Final Answers:
- Q1: \( (2, -1) \)
- Q2: \( (5, 0) \)